UCBG 2-08: 5-year efficacy results from the UNICANCER-PACS08 randomised phase III trial of adjuvant treatment with FEC100 and then either docetaxel or ixabepilone in patients with early-stage, poor prognosis breast cancer. (November 2018) - Campone, Mario; Lacroix-Triki, Magali; Roca, Lise; Spielmann, Marc; Wildiers, Hans; Cottu, Paul; Kerbrat, Pierre; Levy, Christelle; Desmoulins, Isabelle; Bachelot, Thomas; Winston, Tan; Eymard, Jean-Christophe; et al.
Abstract: Purpose: UNICANCER-PACS08 compared adjuvant FEC (5-FU; epirubicin; cyclophosphamide) then docetaxel to FEC then ixabepilone in poor prognosis early breast cancer (BC). We evaluated whether replacing docetaxel with ixabepilone would increase 5-year disease-free survival (DFS). Patients and methods: Triple-negative breast cancer (TNBC) or oestrogen receptor (ER)+/progesterone receptor (PR)−/HER2− BC patients were randomised to receive standard FEC (3 cycles) followed by 3 cycles of either docetaxel (100 mg/m 2 ) or ixabepilone (40 mg/m 2 ). Radiotherapy was mandatory after conservative surgery; ER+ patients received endocrine therapy. Results: Seven hundred sixty-two patients were enrolled between October 2007 and September 2010. Baseline characteristics were balanced between arms. Median follow-up was 66.7 months. Median DFS was not reached; 5-year DFS rate was 76% with docetaxel and 79% with ixabepilone (hazard ratio [HR] = 0.80; 95% confidence interval [CI] = 0.58–1.10; p = 0.175). Median overall survival (OS) was not reached; 5-year OS rate was 86% versus 84% (HR = 0.97; 95% CI = 0.66–1.42; p = 0.897). TNBC patients treated with ixabepilone had a 23% lower risk of relapse compared to docetaxel (HR for DFS = 0.77; 95% CI = 0.53–1.11; p = 0.168). DFS was longer with ixabepilone than docetaxel in patients with grade II–III lymphocytic infiltration (HR = 0.55; 95% CI = 0.29–1.05; p = 0.063). All patients experienced ≥1 adverse events (AEs): 75% reported grade III–IV AEs and two (<1%) had grade V AEs (both with neutropenia and infection receiving ixabepilone). Conclusion: After adjuvant FEC, ixabepilone was comparable to docetaxel for treating poor prognosis early BC patients. The benefit of ixabepilone in subgroups (patients with TNBC and grade II–III lymphocytic infiltration) requires further evaluation. Highlights: Adjuvant chemotherapy is beneficial for breast cancer (BC) patients with poor prognosis. Ixabepilone is an active treatment in advanced BCs. FEC (5-FU; epirubicin; cyclophosphamide) then docetaxel is standard treatment for poor prognosis BCs. FEC then ixabepilone has similar efficacy to standard FEC then docetaxel.